The foundation engineering handbook - Gunaratne, Manjriker (CRC/Taylor & Francis, 2014)
Considering how structures interact with soil, and building proper foundations, is vital to ensuring public safety and to the longevity of buildings. Understanding the strength and compressibility of subsurface soil is essential to the foundation engineer. The Foundation Engineering Handbook, Second Edition provides the fundamentals of foundation engineering needed by professional engineers and engineering students.It presents both classical and state-of-the-art design and analysis techniques for earthen structures and examines the principles and design methods